Recent Progress in Chiral Guanidine-catalyzed Michael Reactions - Yuan, Jiani; Li, Minghua; Ji, Nan; He, Wei; Liu, Yulong (Current Organic Chemistry, 2017)
In recent years, chiral guanidines have attracted considerable interest in organic synthesis because of their unique structural features and strongly basic properties. Compounds belonging to this structural class can act as not only Brønsted bases but also through a hydrogen bond activation mode either of the nucleophile or of the electrophile, and have consequently been widely used in asymmetric organic catalysis, delivering high levels of selectivity and activity. The Michael reaction is one of the most common methods of forming C-C and C-H bonds and has been used in many successful cases as an important transformation of industrial production of several bioactive molecules. In this review, series of classical chiral guanidines with “privileged” scaffolds were summarized, and recent reports describing the usage of chiral guanidines as organocatalysts in enatioselctive Michael reactions of carbon and hetero-nucleophiles to different olefins were described. Furthermore, the transition state models to elucidate how these chiral guanidines affect stereoselectivities in the conjugate additions were demonstrated, and the potential industrial applications of these methodologies were discussed as well.
Keywords: asymmetric synthesis